Peran Media Sosial Dalam Membentuk : Popularitas Budaya Pop Jepang Pada Komunitas Cosplay Yagaro Japanese Club - Sadid Rizqillah Turrahman; RR Roosita Cindrakasih; Rizky Hidayat (CV Edujavare Publishing, 2025)
This study aims to analyze how social media contributes to building the popularity of Japanese pop culture among the younger generation, particularly within the cosplay community of Yagaro Japanese Club. Using a qualitative research method with a descriptive approach, this research explores strategies for utilizing social media, its impact on community identity, and its contribution to the popularity of Japanese pop culture. The findings reveal that social media platforms, especially Instagram, TikTok, and YouTube, play a significant role as promotional and interaction tools for the cosplay community. Through features such as short videos, stories, and collaborations with influencers, this community has successfully expanded the reach of Japanese pop culture both nationally and internationally. Additionally, social media not only facilitates promotion but also strengthens social bonds among community members and supports individual creative expression.